J-conjugate-normal matrices - Kamalvand, Mojtaba Ghasemi; Beiranvand, Parvin Karimi (Sarajevo Journal of Mathematics, 2024)
In this paper some properties of J–conjugate-normal matrices are given. In particular, a list of twenty one conditions is given, each of which is equivalent to the matrix A being J–conjugate-normal. 2010 Mathematics Subject Classification. 15A24, 15B99.